THE INFLUENCE OF CASE BUILDING TECHNIQUE AND LEARNING INTERESTS ON THE STUDENTS’ LEARNING ACHIEVEMENT - Hermansyah, Hermansyah; Jaya, Aswadi; Maharrani, Dwi (English Community Journal, 2021)
This study aims to determine: (1) whether Case building technique and student interest in learning can make a significant difference in improving learning achievement, and (2) the contribution of Case building to increasing student achievement and interest in learning to determine the level of effectiveness of this learning strategy. The data were collected by using a speech test which is evaluated by two assessors using an analytic rubric consisting of five elements, namely accent, grammar, vocabulary, fluency and comprehension. Meanwhile, Student interest in learning was evaluated using a questionnaire. Both data were analyzed using the t-test to see the mean difference (1) between the pre-and post-test students' speaking achievement and their self-confidence, and (2) the post-test of speaking achievement and their self-confidence between the first and second groups. Regression analysis was provided to see the contribution of case building to the variables in question. This study found that case buiding technique could improve the students’ learning interest and learning achievement.